CHARACTERISTICS OF A HARD HEART FROM THE PERSPECTIVE OF TAFSIR AL-AZHAR - Anisah Nur Fauziyyah; Ali Muhammad Asaad; Abdullah Mahmud (Universitas Muhammadiyah Surakarta, 2022)
A study that discusses the characteristics of a hard heart from Hamka's point of view contained in Tafsir al-Azhar as a response to the rampant phenomenon of moral violations that have been generalized by many of the general public. The cause of moral violations is caused by the broken character of society due to several factors including family, education, environment, socio-economic status, and the main factor is the fragile condition of the heart that causes a person to have a hard heart. This research focuses not only on the general definition of a hard heart, but also on the characteristics of a hard heart. Primary and secondary data are used as data sources in the qualitative research method. The main information used comes from the Qur'an, traditions, Tafsir al-Azhar, and additional information in the form of books and various other writings related to the hard heart. The research departs from the interpretation of verses that refer to the definition of qalbun qaswah and qalbun ghaliz, which have the meaning of a hard heart. From these two words, the characteristics of a hard heart were found. In the research, it was found that in general, the main character that most dominates the formation of a hard heart is a closed heart and reluctant to accept invitations to goodness from anywhere, which causes other hard heart characters to arise. Another character of a hard heart that is related to moral violations that often occur in society is the lightness of committing repeated sins. This is stated in the interpretation of Tafsir al-Azhar Surah al-Mā'idah (5): 13.